2018
DOI: 10.4103/njs.njs_39_17
|View full text |Cite
|
Sign up to set email alerts
|

Crash characteristics and pattern of motorcycle related facial bone fractures in a sub-urban Nigerian teaching hospital

Abstract: Context:Recent studies indicated that significant proportion of facial fractures attributed to road traffic mishaps in the middle- and low-income countries are caused by motorcycle (MC) crashes. However, there is limited information on crash characteristics of such injuries. This study was designed to examine the crash characteristics, pattern of fracture, and sociodemographics of patients with facial bone fractures due to MC crashes in our institution.Subjects and Methods:Data on patients’ sociodemographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…The head and neck area is the most exposed area on the body, so it increases the risk of injury in traffic accidents. 26,27,33 The result of statistical analysis in table.6 from differences in the severity of mandibular trauma according to helmet use showed that the MISS (p = 0.199> 0.05) was greater than 0.05.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The head and neck area is the most exposed area on the body, so it increases the risk of injury in traffic accidents. 26,27,33 The result of statistical analysis in table.6 from differences in the severity of mandibular trauma according to helmet use showed that the MISS (p = 0.199> 0.05) was greater than 0.05.…”
Section: Discussionmentioning
confidence: 96%
“…The locations of mandibular fractures based on several studies in developing countries are varied. Obitade et al 26 , report the incidence of mandibular fracture locations in Nigeria from 114 cases are corpus fractures (31.6%) followed by dentoalveolar fractures (21.9%) 33 , Maximina et al 28 , report the mostly affected locations of mandibular fracture are dentoalveolar (14%) as well as parasymphysis and condylus (11%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxillofacial trauma (MFT) is a worldwide public health problem that can result in facial deformation, loss of chewing function, emotional and social impacts (stress, irritability, low self-esteem, and feelings of social exclusion), and high financial costs [ 1 , 2 , 3 , 4 , 5 , 6 ]. Considering the growing industrialization, urbanization, and changes in population profiles, MFT has become one of the major medical problems in emergency rooms [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The type of fracture varies depending on the anatomy of the injured site as well as the magnitude and direction of the force of impact [ 8 ]. According to the literature, facial fractures most commonly affect the mandible, zygomatic bone, and nose [ 4 , 11 , 12 , 13 , 14 ], which are the most exposed regions of the body [ 15 ].…”
Section: Introductionmentioning
confidence: 99%